Pengaruh Terapi Bermain SCL (Snake, Cards, and Ladders) terhadap Keterampilan Mencuci Tangan Siswa Kelas I dan II di SDN Pakusari II Kabupaten Jember (The Effect of SCL (Snake, Cards, and Ladders) Games Therapy to Hand Washing Skill of First and Second G - Nurul Azizah; Tantut Susanto; Latifa Aini Susumaningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Hand washing behaviour in school-age children showed the lowest quality. Prevention effort to improve hand washing skill with SCL (Snake, Cards, and Ladders) games therapy. This study aimed to analyze the effect of SCL (Snake, Cards, and Ladders) games therapy to hand washing skill of first and second grade students in Elementary School of Pakusari II Jember District. The study used pre-experimental with pretest-posttest group design. Sampling technique used simple random sampling with 44 respondents. Data analysis used Wilcoxon Signed Rank Test. Hand washing skill of respondents after games therapy showed 70,4% had good hand washing skill and 29,6% had sufficient hand washing skill. The result showed point p value = 0.000. There was an effect of SCL (Snake, Cards, and Ladders) games therapy to hand washing skills of first and second grade students in Elementary School of Pakusari II Jember District. Recommendation for the school to supply hand washing facility like soap, tissue paper, and hand sanitizer to improve hand washing skill of students in Elementary School of Pakusari II Jember District. Keywords: hand washing, school-aged children, skill, SCL (Snake, Cards, and Ladders), games therapy.